Affect and Nostalgia in Eva Hoffman’s Lost in Translation - Kella, Elizabeth (Studia Anglica Posnaniensia, 2016)
This article examines the affective terrain of Poland, Canada, and the US in Eva Hoffman’s autobiographical account of her migration and exile in Lost in Translation: A Life in a New Language (1989), the text that launched Hoffman’s reputation as a writer and intellectual. Hoffman’s Jewish family left Poland for Vancouver in 1959, when restrictions on emigration were lifted. Hoffman was 13 when she emigrated to Canada, where she lived until she went to college in the US and began her career. Lost in Translation represents her trajectory in terms of “Paradise,” “Exile,” and “The New World,” and the narrative explicitly thematizes nostalgia. While Hoffman’s nostalgia for post-war Poland has sometimes earned censure from critics who draw attention to Polish anti-Semitism and the failings of Communism, this article stresses how Hoffman’s nostalgia for her Polish childhood is saturated with self-consciousness and an awareness of the politics of remembering and forgetting. Thus, Hoffman’s work helps nuance the literary and critical discourse on nostalgia. Drawing on theories of nostalgia and affect developed by Svetlana Boym and Sara Ahmed, and on Adriana Margareta Dancus’s notion of “affective displacement,” this article examines Hoffman’s complex understanding of nostalgia. It argues that nostalgia in Lost in Translation is conceived as an emotion which offers the means to critique cultural practices and resist cultural assimilation. Moreover, the lyricism of Hoffman’s autobiography becomes a mode for performing the ambivalence of nostalgia and diasporic feeling.